2021
DOI: 10.2967/jnumed.121.263082
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Lymphocyte Count After COVID-19 Vaccination Is Associated with Vaccine-Induced Hypermetabolic Lymph Nodes on 18F-FDG PET/CT: A Focus in Breast Cancer Care

Abstract: Rationale: We aimed to predict the presence of vaccine-induced hypermetabolic lymph nodes (v-HLN) on 18 F-FDG PET/CT after Coronavirus disease 2019 (COVID-19) vaccination and determine their association with lymphocyte counts. Methods: In this retrospective single-center study, we included consecutive patients who underwent 18 F-FDG PET/CT imaging after mRNA-or viral vector-based COVID-19 vaccination between early March and late April 2021. Demographic, clinical parameters and absolute lymphocyte count (ALC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…Moderna vaccines have shown to have slightly higher likelihood of nodal reactivity compared to Pfizer vaccine [ 1 ]. A recent retrospective study suggested that lymphopenia maybe associated with lower incidence of nodal reactivity, further supporting the link between nodal reactivity and vaccine immunogenicity [ 11 ].…”
Section: Discussionmentioning
confidence: 85%
“…Moderna vaccines have shown to have slightly higher likelihood of nodal reactivity compared to Pfizer vaccine [ 1 ]. A recent retrospective study suggested that lymphopenia maybe associated with lower incidence of nodal reactivity, further supporting the link between nodal reactivity and vaccine immunogenicity [ 11 ].…”
Section: Discussionmentioning
confidence: 85%
“…The most widely used vaccines were based on messenger ribonucleic acid (mRNA) molecules, which stimulate host cells to synthesize the Spike surface protein of Coronavirus. A large body of data has demonstrated the safety of such vaccines ( Faermann et al, 2021 ; Seban et al, 2021 ). Our patient received the two doses of Pfizer-BioNTech (COMIRNATY) BNT162b2 mRNA between March and April 2021, at the correct 3-weeks interval.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, AC combined with the mRNA Covid-19 vaccine induced a prolonged phase of neutropenia that was probably due to the immune reaction to lymphocyte populations concentrating at peripheral drainage sites. This phenomenon may reflect the relative reduction in peripheral blood and the atypical figures found especially in BC patients following Covid-19 vaccination ( Faermann et al, 2021 ; Seban et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, accompanying manifestations interfered with the diagnosis, including transient fever, decreased white cell and lymphocyte counts, increased inflammatory markers (ESR, PCT, and SF), and abnormal coagulation function. A previous study reported a decrease in lymphocytes after COVID-19 vaccination (26), and elevated PCT and CRP were independent risk factors for death in patients with COVID-19 (47). As all tests for specific infections were negative, and the patient fully recovered without medical intervention, we retrospectively supposed that these manifestations were also vaccine reactions.…”
Section: Concomitant Manifestationsmentioning
confidence: 99%
“…Concerning imaging-detected reactive lymphadenopathy after COVID-19 vaccination, the majority of cases were identified on PET scans, mainly during cancer surveillance. This condition normally involved transient 18-fluorinefluorodeoxyglucose ( 18 F-FDG) uptake in ipsilateral lymph nodes, ranging from intense to gradually regressed after administration (13,19,22,(24)(25)(26). However, the maximal standardized uptake value (SUVmax) should not be solely used to differentiate between benign and malignant lymph nodes (14).…”
Section: Imaging Modalitiesmentioning
confidence: 99%